“I Know That It's Something That's Creating a Bond”: Fathers' Experiences of Participating in Baby Theater With Their Infants in South Africa - Cowley, Brenda; Lachman, Anusha; Williams, Elvin; Berg, Astrid (Frontiers in Psychiatry, 2020)
Abstract In many African countries, particularly those with largely patriarchal societies like South Africa, promoting father-child interaction can pose a challenge. An informative medium that could potentially encourage active participation in pleasurable interactions between fathers and babies may prove to be an important way in which to stimulate fathers’ awareness of their infants’ abilities. Baby Theatre is a production of a Cape Town based theatre company which created the first ever South African baby play for care-givers and their babies between the ages of 2 weeks to 12 months. It is performed in a contained, relaxing space and offers carers and babies time to relate to each other in a pleasurable atmosphere, while specially trained actors’ model sensitive and responsive interactions. Baby Theatre could be a way to encourage fathers’ involvement with their infants, however, no research is currently available documenting fathers’ perceptions about Baby Theatre experience. Aim: To explore fathers’ experience of participating in Baby Theatre. Method: This qualitative study involved six fathers who, with their infants, participated in the Baby Theatre production. A week later the fathers were divided into two focus groups to give them the opportunity to discuss their thoughts about the experience and to reflect on whether it had any subsequent impact on their interactions with their babies. The audio taped, transcribed material was thematically analysed using an interpretative phenomenological approach. Results: The fathers described the experience as educative and enjoyable. They reported that the programme had a positive impact on the way they interacted with their infants and also positively influenced their relationship with them. Additionally, they reported feeling more confident about coping with their babies on their own, and appreciated the connection with the other fathers in the group. Cultural, societal and gender issues were also considered. Conclusions: The subjective experience of the fathers was positive. Further research is needed to assess the lasting effects of the Baby Theatre experience.